2021
DOI: 10.1017/s0007485321000237
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous salicylic acid improves resistance of aphid-susceptible wheat to the grain aphid, Sitobion avenae (F.) (Hemiptera: Aphididae)

Abstract: Salicylic acid (SA), a phytohormone, has been considered to be a key regulator mediating plant defence against pathogens. It is still vague how SA activates plant defence against herbivores such as chewing and sucking pests. Here, we used an aphid-susceptible wheat variety to investigate Sitobion avenae response to SA-induced wheat plants, and the effects of exogenous SA on some defence enzymes and phenolics in the plant immune system. In SA-treated wheat seedlings, intrinsic rate of natural increase (rm), fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…SA acts as a mobile signal molecular for activating SAR because SA accumulates in both the primary infected and systemic uninfected tissue (Malamy et al 1990). For this reason, exogenous SA is commonly used as the activator of plant resistance to biotic stresses (Feng et al 2021). In particular, we showed that exogenous SA with appropriate concentration (1 mM ~ 3 mM) signi cantly activated the resistance of foxtail millet to downy mildew.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…SA acts as a mobile signal molecular for activating SAR because SA accumulates in both the primary infected and systemic uninfected tissue (Malamy et al 1990). For this reason, exogenous SA is commonly used as the activator of plant resistance to biotic stresses (Feng et al 2021). In particular, we showed that exogenous SA with appropriate concentration (1 mM ~ 3 mM) signi cantly activated the resistance of foxtail millet to downy mildew.…”
Section: Discussionmentioning
confidence: 83%
“…For example, SA can enhance tomato plant resistance by modulating the activity of resistance-related enzymes and inducing the expression of pathogenesis-related genes to produce systemic acquired resistance (Li et al 2019). Exogenous SA signi cantly induce resistance of soybean against Fusarium solani infection and wheat variety against aphids (Bawa et al 2019;Feng et al 2021). However, previous studies on the functions of SA in immunity system of foxtail millet have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Plant resistance has been linked to an increase in the defense compounds [ 33 ], and the defensive enzymes associated with the SA and JA pathways play a key role in plant defense against piercing–sucking insects [ 34 , 35 ]. For example, the overexpression of PAL, a rate-limiting enzyme of the SA pathway, can increase plant SA content and increase the mortality of brown planthopper Nilaparvata lugens [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of genes involved in both the JA‐ and SA‐dependent defence pathways of wheat, such as LOX , FAD , PAL and PR1 , are significantly up‐regulated in response to S. graminum infestation (Reddy et al ., 2013 ; Zhang et al ., 2020 ; Zhu‐Salzman et al ., 2004 ). Exogenous application of SA and JA on Arabidopsis , wheat, tomato and Brassica plants had negative effects on aphid population growth (Ali et al ., 2021 ; Boughton et al ., 2006 ; Bruce et al ., 2003 ; Feng et al ., 2021 ). Our results showed that delivery of Sg2204 into wheat suppressed callose deposition and JA‐ and SA‐dependent defence responses induced by nonpathogenic P. fluorescens .…”
Section: Discussionmentioning
confidence: 99%